Critical perspectives on ‘consumer involvement’ in health research: Epistemological dissonance and the know-do gap - Ward, Paul R.; Thompson, Jill; Barber, Rosemary; Armitage, Christopher J.; Boote, Jonathan D.; Cooper, Cindy L.; Jones, Georgina L. (Journal of sociology (Melbourne, Vic.), 2010)
Researchers in the area of health and social care (both in Australia and internationally) are encouraged to involve consumers throughout the research process, often on ethical, political and methodological grounds, or simply as ‘good practice’. This article presents findings from a qualitative study in the UK of researchers’ experiences and views of consumer involvement in health research. Two main themes are presented. First, we explore the ‘know—do gap’ which relates to the tensions between researchers’ perceptions of the potential benefits of, and their actual practices in relation to, consumer involvement. Second, we focus on one of the reasons for this ‘know—do gap’, namely epistemological dissonance. Findings are linked to issues around consumerism in research, lay/professional knowledges, the (re)production of professional and consumer identities and the maintenance of boundaries between consumers and researchers.